Effect of lubricant content to the properties of Fe-based components formed at above ambient temperature - Rahman M.M.; Nor S.S.M.; Ariffin A.K. (Elsevier Ltd, 2023)
This paper presents the outcomes of an experimental investigation on the effect of lubricant content to the mechanical properties and microstructure of components formed at above ambient temperature. A lab-scale uni-axial die compaction rig was designed and fabricated which enabled the powder forming at elevated temperature. Iron powder ASC 100.29 was mechanically mixed with different quantity of lubricant, i.e., zinc stearate for 10, 30, and 60 minutes, respectively. Green compacts were generated by forming the prepared powder mass at 180C through simultaneous upward and downward axial loading. The defect-free green compacts were subsequently sintered in argon gas fired furnace and characterized for their physical and mechanical properties as well as their microstructures were evaluated. The results revealed that the characteristics of final products were affected by lubricant content and mixing time. From this study, the suitable zinc stearate content and mixing time were identified for the production of high quality components through warm forming route. 2013 The Authors. Published by Elsevier.